Konsumsi Alkohol, Obat-obatan Terlarang dan Perilaku Seks Berisiko: Suatu Studi Meta-Analisis - Wahyu Rahardjo (Jurnal Psikologi, 2008)
Risky sexual behavior has been consi-dered as a widespread social phenomenon recently. Its bad consequences bring us to the fact of the increasing of HIV/AIDS cases in the world. Behaviors like condom inconsis-tency, multiple sex partners and dangerous sexual encounters could be shaped by subs-tance use. Substance use itself is consist of the use of alcohol and drugs like marijuana, cocaine, methamphetamine, ecstasy etc. This meta-analysis consist of 101 studies from 30 articles, involving 30136 participants from heterosexual male and female to bisexual and gay male. The result shows positive and significant correlation between substance use and risky sexual behavior. However, this fin-ding supports previous research’s results and also give further insight for other researchers in order to have more concern on other varia-bles for predicting risky sexual behavior. Keywords: substance use, risky sexual behavior, meta-analysis